A Bibliometric Analysis of Online Assessment Platforms in English as a Foreign Language (EFL) Classrooms - Habibie, Alvons; Brianto, Rico (English Education Department, 2023)
This study presents a bibliometric analysis of research on online assessment platforms in English as a Foreign Language (EFL) classrooms, with a focus on Indonesian educational contexts from 2018 to 2022. The analysis highlights the growing recognition of digital tools in enhancing student assessment and learning outcomes. The findings reveal a significant increase in the number of publications on online assessment tools, reflecting the shift toward technology-driven education, especially during the COVID-19 pandemic. Quantitative research methods are predominantly used, emphasizing the objective evaluation of student performance through standardized tests, such as the Cornell Critical Thinking Test (CCTT). However, a noticeable gap exists in qualitative research, which could provide deeper insights into the contextual factors affecting the effectiveness of these tools. Additionally, the study identifies concerns regarding the transparency of data collection instruments, particularly their validity and reliability. The study concludes that while quantitative approaches dominate the field, there is a need for more balanced research methodologies and rigorous validation of assessment tools to ensure credible and comprehensive insights into the role of online assessments in EFL education.